Fostering EFL Learners’ Critical Thinking Skills in Reading Classes through the Use of Graphic Organizers - Wijaya, Kristian Florensio (EDUCAFL: Journal on Education of English as Foreign Language, 2024)
To make the best use of the utmost reading learning outcomes, second language educationalists are highly supervised to collate the mutual interplay between their traditionally-implemented reading approaches with learner-oriented methods. One of the probable student-centered reading learning strategies rewarding to be applied in these modern EFL reading enterprises is graphic organizers. Previous researchers held a strong contention that graphic organizers strategy could supportively assist EFL learners in infusing the significant development of critical thinking skills as they were freely permitted to enact their creative, representative, and engaging graphic displays that are relatable to their presently-situated reading texts. This present small-scale library study was commenced to profoundly investigate how graphic organizers strategy can promote significant critical thinking skills growth among second language learners in reading classes. To actualize this study objective, the researcher thematically subdivided the similarly-shared research results derived from 20 previous graphic organizer investigations into some main particular themes to yield more comprehensible and credible research outcomes. The thematically-analyzed research results unraveled that the graphic organizers strategy helped EFL learners to transform into highly-achieving and motivated readers; two essential components ingraining the maximization of critical thinking skills growth within language learners’ reading learning journeys.